On the classical groups of mathematical physics - Vera Saravia, Edgar Diógenes (2020)
Starting from Pauli and Dirac matrices of 1928 we present a friendly and unified version of the classical groups of mathematical physics as subgroups of sub algebras of real geometric algebras, created and presented for Clifford in 1879, the prior concept of Clifford algebras.